MATHEMATIC COMMUNICATION SKILLS IN SENIOR HIGH SCHOOL BASED ON GENDER DIFFERENCES - Harfin Lanya; Moh. Zayyadi; Septi Dariyatul Aini; Haris (Pi: Mathematics Education Journal, 2020)
This study aims to describe and analyze the written mathematical communication of high school students on linear program questions based on gender. This research was conducted at SMAN 3 Pamekasan class XI MIPA I. The subjects in this study were 2 students out of 32 students of class XI MIPA I who were the superior class of mathematics selected by purposive sampling. This research uses descriptive research with a qualitative approach. The instruments used were Mathematics Ability Test, written Mathematical Communication Test and Interview Guidelines. Data were analyzed descriptively in the form of qualitative data obtained from the results of the Written Test to describe students' written mathematical communication. The results showed that female students were more dominant than male students in the cognitive domain and completed written math problems in full.